SYNTHESIS OF MAGNETITE/ACTIVATED CARBON NANOCOMPOSITES FOR THE REMOVAL OF LEAD AND METHYLENE BLUE - Mina Devika Setiana; Yap Wing Fen; Arif Hidayat; ST. Ulfawanti Intan Subadra; Ahmad Taufiq (Universitas Mataram, 2026)
Water pollution from industrial waste, such as lead and methylene blue (MB), has serious impacts on aquatic life and human health. In addition, existing methods are less effective for waste treatment and are costly to operate. Therefore, this study aims to develop magnetite/activated carbon nanocomposites based on natural materials as adsorbents. The XRD diffraction pattern showed broadened peaks and the highest crystalline peaks at 2θ = 20°–26° and 35.5° for activated carbon and magnetite, respectively. The nanocomposite formation was confirmed from the EDX spectrum, which showed the presence of Fe, O, and C elements, as well as from the FTIR spectrum, which detected the presence of Fe–O, C–H, C=C, C=O, and O–H functional groups. Furthermore, based on the SEM results, the nanocomposites were found to be spherical and porous, with an average particle size of 35.53 ± 0.83 nm. Meanwhile, the BET results showed that the nanocomposites had a total pore volume of 0.333 cm3/g. The kinetics of lead adsorption reached equilibrium in 25 minutes with an efficiency of 99.51%. The adsorption of MB reached equilibrium in 20 minutes, with an efficiency of 97.02%. The results of the kinetic analysis showed that the adsorption of lead and MB both fit the pseudo-second order (PSO) modeling with adsorption capacities (qe) of 11.6550 mg/g and 7.3421 mg/g, respectively. Based on these results, the magnetite/activated carbon nanocomposites are promising as an alternative adsorbent due to their high efficiency, practicality, and magnetic separation capabilities.